A PRÁTICA DO LIAN GONG NA PROMOÇÃO DE SAÚDE - de Freitas Sousa, Karen; Vicente Torres, Michelle; Nascimento Rabelo, Matilde; da Silva Melo, Larissa; Carvalho dos Santos, Bárbara; da Silva Guimarães, Joana Maria (SANARE - Revista de Políticas Públicas, 2015)
-